Optimal Scheduling of Power Systems Using Asymmetric Nash Cooperative Game Based on Bankruptcy Theory Under Extreme Weather Conditions - Yanbo Zhan; Zhigang Lu; Liangce He; Jiangfeng Zhang; Xueping Li; Xiaoqiang Guo (IEEE Access)
In recent years, large-scale power outages due to climate change have occurred frequently worldwide, causing significant economic losses and severe social impacts. Against the backdrop of extremely cold weather in northeastern China. This paper presents a new operating model using asymmetric Nash cooperative game theory and resource bankruptcy theory to minimize power system operating costs under extreme weather conditions. Firstly, a fair power allocation model based on the principle of minimum variance is used to determine the boundary conditions of power resource allocation. Secondly, an asymmetric Nash cooperative game model based on bankruptcy theory is constructed for two load response modes. Then, a comprehensive bargaining weight calculation method is proposed for the negotiation of power resource allocation among various types of users by taking into account the actual demands of various users and economic factors. According to the load response game, a cost minimization power system scheduling model is derived by combining thermal power, wind power, photovoltaic power, and pumped storage. Four scenarios are investigated in the case study. The results show that the proposed model can improve fairness and satisfaction while reducing load response costs.